Intersexuality associated with XX/XY mosaicism in a horned goat - Bongso, T.A.; Thavalingam, M.; Mukherjee, T.K. (Karger AG, 1982)
Anatomical, histological, and cytogenetic studies were undertaken on a horned intersex goat kid and three of its normal litter mates. The intersex had male type horns, male beard, vestigial mammary glands, female external genitalia, and an enlarged peniform clitoris, exuded a pungent male odor, had a male bleat, and came into estrus every 20 days. At laparotomy and subsequent slaughter, an ovotestes was observed on the right side and a testis and epididymal remnants on the left side. Uterine horn segments, cervix, vagina, and enlarged clitoris (2 cm) were also present. Histologically, spermatogenesis was not observed in either testis, but active Leydig cells were present. The ovary contained mature follicles. Chromosome analysis revealed 60XX/60XY cell populations in blood, bone marrow, and skin. Lymphocytic metaphases from the male and female cosibs showed single populations of 60XY and 60XX, respectively. Mosaicism associated with the horned condition in the intersex goat was established.